Supraglottic subepithelial benign mass lesions: Focus on clinical features of sialolipoma-like lesion. Issue 1 (February 2021) - Tachibana, Tomoyasu; Kariya, Shin; Wani, Yoji; Komatsubara, Yasutoshi; Naoi, Yuto; Kuroda, Kazunori; Fushimi, Soichiro; Hotta, Machiko; Haruna, Katsuya; Nagatani, Tami; Makino, Takuma; Kataoka, Yuko; et al.
Abstract: Objectives: Sialolipoma has been classified as a benign soft tissue lesion in the 2017 World Health Organization classification of head and neck tumors. To our knowledge, only one case of laryngeal sialolipoma has been reported in the English literature. We conducted a retrospective study to identify clinical characteristics of supraglottic sialolipoma-like lesion and differentiate it from other supraglottic subepithelial masses. Methods: Medical records of 16 patients with supraglottic subepithelial benign mass lesions who underwent histological evaluation between 2003 and 2019 were retrospectively analyzed. Sialolipoma-like lesion was defined as a local finding of a well-circumscribed gross mass with pathological presence of salivary gland-like parenchymal lobules with evenly interspersed adipose tissue. Results: Eight patients showed histological positivity for sialolipoma-like lesion, 3 for amyloidosis, 2 for hemangioma, and 1 each for cyst, lymphoid hyperplasia, and chondrometaplasia. Sialolipoma-like lesion tended to be predominant among men; those affected had a mean age of 52.8 (range, 39–74) years. By contrast, among patients with amyloidosis, the ratio of men to women was 1:2 (100% vs. 33%; p = 0.055). Fiberscopic examination of all patients with sialolipoma-like lesions identified well-circumscribed, yellowish masses, closely resembling local amyloidosis findings. Sialolipoma-like lesion was associated with a significantly higher body-mass index (BMI; 27.4 ± 2.8 kg/m 2 ) than amyloidosis (21.6 ± 1.4 kg/m 2 ; p = 0.014). The transoral approach was used for lesion resection in all patients with sialolipoma-like lesion. No patient experienced postoperative recurrence. Conclusion: Laryngeal sialolipoma-like lesion might be more prevalent than was previously reported, and histological examination is important to differentiate it from amyloidosis. Supraglottic sialolipoma-like lesion must be differentially diagnosed in patients with high BMI presenting with well-circumscribed, yellowish supraglottic masses.